Diseminasi Strategi Penggalangan Dana melalui Kaleng Koin untuk Lembaga Filantropi Islam Baru di Kota Bengkulu - Nafsih, Syarifatun; Rahayu, Putri Rezeki; Rahmat, Ihsan (Jurnal Pengabdian Kepada Masyarakat, 2024)
Indonesia is still the most generous country in the world supported by Muslim behaviour and philanthropic institutions. The presence of philanthropic institutions on the one hand helps the welfare of society, but on the other hand, it leaves various problems. This dedication aims to explain and describe fundraising strategies through coin cans. Two philanthropic institutions that have become partners in the Da'wah Management Study Program at UIN Fatmawati Sukarno Bengkulu were involved: Yayasan Darul Armina and Bait Zakat. The method used is dissemination where lectures and interaction in the form of questions and answers are the mainstay. Implementation of service is carried out in three stages: determination, implementation and evaluation. The determination stage starts with determining the core of the service, mapping problems, determining service topics, and coordinating institutions. The implementation phase begins with a presentation of the material and continues with questions and answers and discussion. The evaluation stage looks at the success of service activities. Finnaly, this activity provides recommendations for future service that it is important to continue the practice and mentoring of Islamic philanthropic institutions